Psychological features of perception and experience of solitude by teenagers - Diachok, Olga (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article analyzes the approaches to the definition of "loneliness". We consider the experience of loneliness as a problem in adolescence.The results of empirical research experience of solitude teenagers demonstrated the connection loneliness with vitality. In the article also analyzed perception of loneliness in adolescence.
Keywords: loneliness; adolescence; vitality; inclusion; control; acceptance; dependence on communication; positive loneliness